Management of Cucumber Mosaic Virus (Cmv) Infecting Cucumber in Bangladesh (Bangladesh Journal of Agricultural Research, 2022)
Cucumber mosaic virus (CMV) is the most important and widespread virus. It attacks cucumber (Cucumis sativus) causingsevere yield loss. A research project was undertaken with a view to developing appropriate management option against CMVof cucumber in Bangladesh.Six integrated disease management packages were tested under field condition. A non-treated control was included for comparison with the packages. The experiment was conducted in the research field of Bangladesh Agricultural Research Institute, Gazipur during rabi season of 2018. All the treatment packages appreciably reduced CMV incidence of cucumber over control. Disease incidence was reduced to 35.71 to 76.97% over control and yield was increased to 0.37 to 6.40 t/h due to all treatment combinations compared to control. Two treatment packages T2- Netting seedling, sticky yellow trap, polythene mulch and 4 sprays of Imidacloprid 0.1 % at 15 days interval and T1- T2+Bio-neem0.2 % instead of Imidacloprid were considered as the most effective management options on the basis of minimum disease incidence (9.67; 10.5), higher yield (13.04 t/ha; 12.96 t/ha) and Marginal benefit cost ratio (1:3.17&1:2.93), respectively. Marginal cost benefit analysis indicated that the two management packages T1and T2may be economically viable and cost effective.These management packages may be recommended for management of CMV infecting cucumber.Bangladesh J. Agril. Res. 45(1): 65-76, March 2020